POTENSI TUMBUHAN LAHAN RAWA SEBAGAI PUPUK ORGANIK - Hikma Ellya; Ronny Mulyawan; Novianti Adi Rohmanna (Agrisains: Jurnal Budidaya Tanaman Perkebunan Politeknik Hasnur, 2020)
Some plants in swamps are a problem because the growth rate is relatively fast, such as water chestnut (Eleocharis dulcis), kalakai (Stenochlaena palustris), and water hyacint (Eichornia crassipe)s. Therefore, various technologies are always traced to increase the use value of these swamp plants. One of the uses is by making organic fertilizer to support the availability of nutrients for plants. The purpose of this study is to utilize swamp plants and compare the pH, C-organic, N-total and C / N ratio values ??of each swamp plant. The study was conducted at the Soil Laboratory of the Faculty of Agriculture, University of Lambung Mangkurat in October - November 2014. The study used a single, completely randomized design (CRD). The factors studied were swamp plant organic material consisting of 3 treatments, namely: B1 (rat purun); B2 (kalakai); and B3 (water hyacinth). Each treatment was repeated 6 times, so that 18 experimental units were obtained. The results showed that water water hyacint had the highest N-total and the lowest C / N ratio compared to kalakai and water chestnut.